2015
DOI: 10.1093/cvr/cvv213
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4 in cardiac electrical activity

Abstract: TRPM4 forms a non-selective cation channel activated by internal Ca(2+). Its functional expression was demonstrated in cardiomyocytes of several mammalian species including humans, but the channel is also present in many other tissues. The recent characterization of the TRPM4 inhibitor 9-phenanthrol, and the availability of transgenic mice have helped to clarify the role of TRPM4 in cardiac electrical activity, including diastolic depolarization from the sino-atrial node cells in mouse, rat, and rabbit, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 96 publications
1
81
0
Order By: Relevance
“…40,41 However, the membrane potential changes which last tens of seconds ( Figure 1C) evidence in favor of electroporation. It could be due to either plasma membrane electroporation or opening of nonselective channels, like TRPC3, TRPC6, or TRPM4 associated with electrophysiological effects in the myocardium.…”
Section: Discussionmentioning
confidence: 98%
“…40,41 However, the membrane potential changes which last tens of seconds ( Figure 1C) evidence in favor of electroporation. It could be due to either plasma membrane electroporation or opening of nonselective channels, like TRPC3, TRPC6, or TRPM4 associated with electrophysiological effects in the myocardium.…”
Section: Discussionmentioning
confidence: 98%
“…Excessive activation of TRPM4 is associated with various non‐malignant disorders and has been proposed to be a putative target for inhibition in numerous cardiovascular disorders and hypertension, oxidative stress‐mediated inflammatory diseases and multiple sclerosis . Trpm4 −/− mice were shown to be viable and fertile without obvious anatomical abnormalities, TRPM4‐selective inhibitor 9‐phenanthrol exerted cardioprotective effects, while the Human Protein Atlas consortium included TRPM4 as one of the 1054 potentially druggable proteins of the human proteome, indicating that TRPM4 represents a potential experimental target.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive activation of TRPM4 is associated with various non-malignant disorders and has been proposed to be a putative target for inhibition in numerous cardiovascular disorders and hypertension, [45][46][47][48][49] oxidative stress-mediated inflammatory diseases 10 and multiple sclerosis. 50 Trpm4 À/À mice were shown to be viable and fertile without obvious anatomical abnormalities, 51 TRPM4-selective inhibitor 9-phenanthrol We demonstrated that TRPM4-positive DLBCL patients treated with R-CHOP exhibited significantly worse survival, consistent with its expression being associated with adverse clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“… a ; Kruse & Pongs, ; Guinamard et al . ). More specifically, the TRPM4 mRNA relative expression in non‐diseased human hearts indicates that it is expressed more in PF than in septum, atrium and ventricles (Kruse et al .…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, the heart is known as a major TRPM4 mRNA expressing tissue (Launay et al 2002;Nilius et al 2003;Mathar et al 2014a;Kruse & Pongs, 2014;Guinamard et al 2015). More specifically, the TRPM4 mRNA relative expression in non-diseased human hearts indicates that it is expressed more in PF than in septum, atrium and ventricles (Kruse et al 2009).…”
Section: Introductionmentioning
confidence: 99%